2019
DOI: 10.1071/sh17119
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of selected quality of life domains in patients who have undergone conservative or radical surgical treatment for penile cancer: an observational study

Abstract: Background Surgery is the standard treatment for organ-restricted penile cancer, but it is also a disfiguring procedure that can profoundly affect quality of life. Using a survey, in this study we assessed the effect of different surgical invasiveness on satisfaction in selected life domains of patients who underwent penile-sparing surgery and partial penectomy. Methods: Forty patients who underwent penile-sparing surgery (n=13) or partial penectomy (n=27) were enrolled in the study. The response rate was 71%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Notably, no statistically significant difference was noted in the domains of erectile function, sexual desire, overall sexual satisfaction, or intercourse satisfaction; however, those treated with partial penectomy reported a higher degree of appearance concerns than their counterparts. A Polish study by Sosnowski et al reported similar outcomes (31). Using the IIEF, the authors assessed sexual outcomes in 40 men using validated questionnaires in sexually active patients who underwent circumcision/WLE and partial penectomy.…”
Section: Partial Penectomymentioning
confidence: 87%
“…Notably, no statistically significant difference was noted in the domains of erectile function, sexual desire, overall sexual satisfaction, or intercourse satisfaction; however, those treated with partial penectomy reported a higher degree of appearance concerns than their counterparts. A Polish study by Sosnowski et al reported similar outcomes (31). Using the IIEF, the authors assessed sexual outcomes in 40 men using validated questionnaires in sexually active patients who underwent circumcision/WLE and partial penectomy.…”
Section: Partial Penectomymentioning
confidence: 87%
“…Overall 3283 abstracts were screened and 235 studies were retrieved for full-text screening. Eighty-eight studies including 9758 patients were eligible for assessment: 16 NRCSs (1911 patients) [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] and 72 CSs (7864 patients) [6] , [7] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , …”
Section: Evidence Synthesismentioning
confidence: 99%
“…The baseline characteristics of NRCSs and CSs are presented in Table 2 , Table 3 . All 16 NRCSs were retrospective studies, 12 comparing penile-sparing surgery with amputative surgery [11] , [12] , [13] , [14] , [15] , [16] , [17] , [20] , [21] , [22] , [24] , [25] and four comparing radiotherapy with penile surgery [10] , [18] , [19] , [23] . All 72 CSs were retrospective, with 39 studies addressing penile surgery [6] , [7] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , 20 reporting on radiotherapy [26] , [27] , [28] , [29] , [30] , [31] ...…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the quality of life could be the best described as statistical index which is based on various parameters, like economic related, health related and environmental related [9] . Poor social networks [10] and additional contributing features such as poor living conditions, poverty and poor social relations [11] underwrite deterioration in quality of life.…”
Section: Introductionmentioning
confidence: 99%